Synthesis of polyhydroxylated flavonoids - Ahmad, Farediah; Mohd. Sirat, Hasnah; Azahar, Muhammad Syamil; Mohamed Adib, Adiana (Faculty of Science, 2009)
Flavonoids are a group of polyphenolic compounds ubiquitously found in the plant kingdom. Flavonoids have gained recent interest because of their broad pharmacological activities. In the present study, several polyhydroxylated flavonoids namely, 3,4-bis(benzyloxy)-3-hydroxyflavone, 3,4,5,7-tetrahydroxyflavanone, 4,5,7-trihydroxyflavanone and 4,5,7-trihydroxy-3-prenylflavanone have been synthesised. These target compounds were synthesised via its chalcones as the key precursor. The initial step in the synthesis was to prepare various derivatives of 2- hydroxyacetophenone and benzaldehyde by protection of the phenolic hydroxyl groups. The approach for the synthesis of chalcones is by the Claisen-Schmidt condensation of the respective 2-hydroxyacetophenones and benzaldehydes under basic condition to give the corresponding 2-hydroxychalcones. 3,4-Bisbenzyloxy- 3-hydroxyflavone was synthesised from 3,4-bis(benzyloxy)-2-hydroxychalcone by the Algar-Flynn-Olyamada (AFO) oxidative method. The natural occurring flavanones, 3,4,5,7-tetrahydroxyflavanone and 4,5,7-trihydroxyflavanone were prepared from 2-hydroxy-3,4,4,6-tetrakis (methoxymethyloxy)chalcone and 2- hydroxy-4,4,6-tris(methoxymethyloxy) chalcone respectively, by acid hydrolysis and subsequent treatment with sodium acetate. The last feature in the synthesis was the preparation of 4,5,7-trihydroxy-3-prenylflavanone starting from the prenylation of 4-hydroxybenzaldehyde, protection of the phenolic group, formation of 2- hydroxy-4,4,6-tris(methoxymethyloxy)-3-prenylchalcone and followed by acid hydrolysis and cyclisation of the chalcone led to the production 4,5,7-trihydroxy-3- prenylflavanone in 89.3% yield. The antibacterial activity of the targeted compounds and its chalcone precursor were demonstrated by the filter paper disc diffusion method. The antioxidant activity were evaluated based on the free radical scavenging activity of the flavonoids against 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical by using UV and Electron Spin Resonance techniques. Structures were confirmed spectroscopically by UV, IR, NMR (1H and 13C), COSY and MS.